Identidades, imagens e papéis museais nos discursos institucionais sobre a relação museu-escola - Mariana de Queiroz Bertelli (2010)
This paper studies the relationship between museum and school in the context of educational policies. The research aimed to investigate museums identities, images and roles in the institutional discourses of museum and school. Museum discourse was analyzed by educational policies of a science museum in Belo Horizonte, Minas Gerais state. Three different curriculum policies scopes - national, state and municipal - represented the school discourse, named: Parâmetros Curriculares Nacionais for national context, Conteúdos Básicos Comuns from Minas Gerais state and Proposições Curriculares from Belo Horizonte city. We used only the final grades of elementary school curriculum. Datacollection included a documentary research and a semi-structured interview. Content Analysis method was applied to analyze textual documents and interviews discourses. The results indicated inconsistencies between curriculum and museum policies. When considering museum, there was an emphasis on its social and educational aspects, and an effort towards public approachment, especially scholar. Meanwhile, curriculum proposals ignore themuseum educational identity, highlighting, in most cases, just as a complementary function of school education with the role of a mere place for school visits. This work contributes to a better understanding of issues related with the tension relationship between museum and school and also to broaden the debate on the institutionalization of this relationship.